Study on the Use of Eco-Enzyme in the Cleaning Process of Houses of Worship at Isa Al-Masih Church Tikala Manado - Sri Martini; Efraim Laluas; Christina Rawung (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
This study aims to analyze the effectiveness of eco-enzyme as a natural cleaning agent in maintaining the cleanliness of the House of Worship at the Church of Isa Al-Masih Tikala, Manado. The research employed a qualitative descriptive method, involving observations, interviews, and practical trials of eco-enzyme application in various church areas such as floors, toilets, windows, and worship equipment. Data was collected from church leaders, caretakers, and congregation members. The findings reveal that eco-enzymes are effective in removing light to moderate dirt and organic residues, while also eliminating unpleasant odors naturally without leaving harmful chemical traces. Compared to conventional chemical cleaners, eco-enzymes provide significant health and environmental benefits, being non-toxic, biodegradable, and safe for continuous use. Additionally, its use contributes to the reduction of organic waste, as it is made from fermented fruit and vegetable scraps. Community responses indicate positive acceptance, although further education and socialization are needed to increase awareness and consistent use.